4.6 T generated by a high-temperature superconducting ring magnet. (9th March 2020) - Ali, Muhammad Zulfiqar; Zheng, Jinxing; Huber, Felix; Zhang, Zhiwei; Yuan, Weijia; Zhang, Min
Abstract: We report here a record 4.6 T trapped field generated by high temperature superconducting (HTS) persistent current loops using a HTS ring structure. By stacking 200 HTS rings into a compact magnet 90 mm in diameter, we performed a field cooling magnetisation at 25 K. The main advantage of the new magnet compared to existing trapped field HTS magnets is that the magnetic field is in the parallel direction to the ab plane of the HTS, leading to higher critical currents in the same magnetic field. Therefore, compact HTS magnets can be developed based on this principle to achieve high magnetic fields. Experimental results show that the final trapped field distribution depends on the ring geometry. We developed a new three dimensional model to simulate the magnetic field distribution within the HTS ring magnet and good agreement between experiments and simulation have been found. The temperature dependency and ramping rate dependency have been studied numerically as potential factors to influence the magnet field. The proposed HTS ring magnet will have promising applications in medical imaging devices, e.g. MRI, as well as electrical machines.